Physical Modelling of Earthquake-induced Liquefaction on Uniform Soil Deposit and Earth Structures Settlement - Avantio Pramaditya; Teuku Faisal Fathani (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2021)
Earthquake-induced liquefaction has been a complex and challenging topic in the field of geotechnical engineering due to its ability to cause catastrophic damage to the surrounding area. The manifestation of earthquake-induced liquefaction as observed from the effect of its past occurrence is damages on the ground and structures such as buildings, earth structures, and important lifelines structures. Liquefaction is caused by the loss of strength and stiffness of the cohesionless saturated soils due to the rapid dynamic loads from the earthquake. However, its complexity and uncertainty make the problems as one of the challenging problems in geotechnical engineering. One of the method to analyse the phenomena is through Physical modelling. Model subjected to the geotechnical centrifuge is required to analyse and observed the earthquake-induced liquefaction phenomena and this study aimed to understand the liquefaction phenomena, mechanism, and consequences through physical modelling by centrifuge and laboratory tests. This involved the physical modelling of the embankment which lies on a liquefiable foundation ground and subjection to earthquake motion of the 2011 Tohoku Earthquake retrieved from K-Net Mito stations. Moreover, geotechnical centrifuge test with 50 g of centrifugal acceleration was conducted to create the conditions of the actual field and the behaviour of the model related to acceleration, pore pressure, and displacement was observed using sensors. The liquefaction manifestation was observed in the model with the occurrence of lateral spreading, remnants of the sand boils, and deformation of the embankment. Furthermore, excess pore water pressure was rapidly developed and the pore pressure ratio (ru) higher than 1 was found to have indicated the occurrence of liquefaction while the embankment settle was estimated at 0.43 m.